The costs of a multisectoral nutrition program implemented through a poultry value chain platform in Burkina Faso - Margolies, Amy; Pedehombga, Abdoulaye; Twalibu, Aisha; Nwabuikwu, Odiche; Wun, Jolene; Kemp, Chris; Gelli, Aulo; Levin, Carol (Wiley, 2025)
Undernutrition in women and young children in Burkina Faso is a critical problem. Egg consumption is low despite many households raising poultry. The Soutenir l'Exploitation Familiale pour Lancer l'Élevage des Volailles et Valoriser l'Économie Rurale (SELEVER) project, an integrated agriculture-nutrition intervention, promoted egg consumption and sales to investigate the impact of poultry production on child nutrition. Multisectoral nutrition-sensitive agriculture programs address nutrition deficits but lack comparable cost information. This study estimates the costs of the SELEVER program, an integrated poultry and nutrition intervention. The study estimates the program's economic costs using a standardized methodology from the Strengthening Economic Evaluation for Multisectoral Strategies for Nutrition (SEEMS-Nutrition) consortium, which aligns financial and economic costs along program impact pathways, allocating costs by activities and inputs. We conducted qualitative interviews and focus groups on time allocation and beneficiary out-of-pocket costs. Incremental economic costs were calculated by combining expenditures and economic costs. The total incremental program cost was USD$18,084,727.68 over 5 years, with annual incremental costs of USD$209.20 per direct beneficiary and $796.26 per household. Major cost drivers included overhead (18%), poultry extension (17%), training (16%), household counseling (7%), technical assistance (7%) and microcredit (6%). Total input costs were dominated by personnel (51%), supplies (13%), agricultural inputs (10%) and overhead (9%). We present the total incremental costs of a multisectoral nutrition intervention to generate revenue with poultry. The costs per beneficiary were higher than similar interventions, underscoring the need for cost-effectiveness evaluations of multisectoral nutrition programs. A standardized cost methodology facilitates comparisons with multisectoral nutrition interventions and builds the evidence base.